Quantifying exhumation at the giant pulang porphyry Cu-Au deposit using U-Pb-He dating - Leng, C.; Cooke, D.; Hou, Z.; Evans, Noreen; Zhang, X.; Chen, W.; Danisik, Martin; McInnes, Brent; Yang, J. (Society of Economic Geologists Inc, 2018)
The Triassic Pulang porphyry Cu-Au deposit, located in the South Yidun terrane, is the oldest and one of the largest porphyry deposits in the southeastern Tibetan Plateau. The mineralization occurs mostly in the potassic alteration zone of the Pulang intrusive complex. U-Pb-He triple dating, namely apatite (U-Th)/He, zircon U-Pb, and zircon (U-Th)/He dating, together with inverse thermal modeling, reveals that the Pulang complex was emplaced at a paleodepth of ~5.0 to 6.5 km at 215 ± 2 Ma. The deep-level emplacement of the complex, coupled with the episodic replenishment of the magma chamber, gave rise to the establishment of a prolonged magmatic-hydrothermal system at Pulang. Although a range of single-grain zircon and apatite (U-Th)/He ages were obtained on each sample, the weighted mean zircon and apatite (U-Th)/He ages vary systematically with elevation, defining a multistage cooling/denudation history at Pulang. Specifically, three phases of cooling were recognized from inverse thermal modeling, including rapid cooling (80°–120°C/m.y.) in the Late Triassic, moderate cooling (3°–5°C/m.y.) from the Late Triassic to Early Cretaceous, and a protracted slow cooling period (<1°C/m.y.) from the Early Cretaceous to the present day. The first phase of cooling can be mainly attributed to magmatic cooling, whereas the later two phases of cooling were predominantly controlled by uplift and denudation processes. Moreover, the remarkable decrease in the cooling rate from the second to the third phase can be linked to a decreasing erosion rate during the third phase, supported by age-elevation relationships. Overall, our results indicate that the Pulang complex experienced two stages of exhumation at 33 to 45 m/m.y. and 5 to 17 m/m.y. Based on these data, we estimate that approximately 558- to 1,099-m thickness of materials have been removed from the Pulang complex during uplift and erosion, including a large volume of ore. The long time span (>50 m.y.) of extremely slow cooling and erosion at Pulang could be related to the formation and preservation of a peneplain on the southeastern Tibetan Plateau since the Late Cretaceous. A relict peneplain thus signifies a favorable tectonic environment for the preservation of ancient porphyry systems worldwide.